THE EFFECT OF TAX AVOIDANCE AND CORPORATE GOVERNANCE ONFIRM VALUE WITH SUSTAINABILITY REPORTING AS MODERATION - Hendi; Winny; Harsono, Budi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
The research employs Sustainability Reporting as a moderating variable. We aim to discover of Sustainability Reporting roles on the influence of Tax Avoidance and Corporate Governance on Firm Value. This research is a quantitative study with a data panel analysis. The sample used in this study was data from financial reports of financial sector companies published on the Indonesia Stock Exchange website from 2018 to 2021. The sample was selected from 94 companies using a purposive sampling technique. The data are analyzed using panel regression models. Research findings reveal that tax avoidance and corporate governance do not have a significant effect on firm value, and tax avoidance and corporate governance on firm value moderating by sustainability reporting also have no significant effect on firm value. This is because the financial sector consists mostly of banks, subject to stricter supervision than other sectors, so many data measurements are difficult to obtain. The research delivers understanding and information on behalf of the influence of tax avoidance and corporate governance with sustainability reporting as moderating on firm value, particularly for the financial sector in Indonesia.